(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article examines the function of space in the novels of Charles Dickens, arguing that place in his work is never morally neutral but always carries an ethical charge. One of the most stable principles of Dickensian poetics is the endowment of space with moral meaning: dwellings, towns, courts and prisons are organized into a coherent “moral topography” in which the description of a place becomes a form of ethical judgement. Drawing on Hard Times (1854), Bleak House (1852–1853), Great Expectations (1860–1861) and the wider corpus, the study distinguishes between the spaces of evil — the industrial town, the court, the prison, the slum — and the spaces of good, associated with the warm and living home, and it shows how, in the mature fiction, this stable topography begins to dissolve. The analysis employs close reading and structural-semantic methods. The findings indicate that moral topography is a constitutive element of Dickensian poetics, that it translates abstract social criticism into concrete sensory image, and that its gradual destabilization corresponds to the deepening complexity of the writer’s moral vision. The study contributes to an understanding of the chronotope as a bearer of ethical meaning in the Victorian novel.